How can digital finance release the ecological value of land intensification: the insight of urban ecological resilience - Li, Yarong; Liu, Chengxin; Hu, Zijing; Li, Jiawei (Frontiers in Environmental Science, 2025)
As a substantial developmental framework aimed at tackling environmental challenges, the development of intensive use of urban land (IUUL) has yet to actualize its ecological efficacy fully. Improving the spatial distribution of factor resources can play a pivotal role in unlocking the ecological potential of IUUL, with a special emphasis on the effective allocation of financial resources. The emergence of digital finance (DF), such as Alipay and Pocket Banking, has notably enhanced the efficiency of financial resource allocation. Nonetheless, empirical data concerning the ability of DF to enhance the ecological significance of IUUL are scarce, and the mechanisms driving these processes remain obscure. This research utilizes panel data from 282 prefecture-level cities spanning 2011–2020 to explore the potential of DF in enhancing the ecological value of IUUL through the lens of urban ecological resilience (UER). The results suggest that DF has the potential to significantly enhance the positive impacts of IUUL on UER significantly, thereby further unlocking the ecological value of IUUL. Mechanisms analysis reveals the potential of DF to unlock the ecological value of IUUL by fostering regional green innovation (GI), rationalizing industrial structure (RIS), and overall upgrading of industrial structure (OUIS). Moreover, the heterogeneity analysis suggests that the effect is more prominent in economically advanced eastern regions, regions with more comprehensive infrastructure, and regions with more favorable innovation environments. This paper highlights the potential of DF to enhance UER through IUUL, offering empirical evidence for the profound fusion of the digital economy and the real economy to drive green transformation. It also charts a course for the real economy’s green transformation and the sustainable development of the economy.